A Novel Porcine Model of Ischemia-Reperfusion Injury After Cross-Clamping the Thoracic Aorta Revealed Substantial Cardiopulmonary, Thromboinflammatory and Biochemical Changes Without Effect of C1-Inhibitor Treatment - Nielsen, Erik Waage; Miller, Yoav; Brekke, Ole-Lars; Grond, Joost; Duong, Anh Hoang; Fure, Hilde; Ludviksen, Judith Krey; Pettersen, Kristin; Reubsaet, Leon; Solberg, Rigmor; Johansen, Harald Thidemann; Mollnes, Tom Eirik (Frontiers in Immunology, 2022)
Ischemic injury worsens upon return of blood and innate immunity including the complement system play a central role in ischemia-reperfusion injury (IRI) as in thoracic aortic surgery. Complement component1 inhibitor (C1-INH) has been shown to reduce IRI and is a broad-acting plasma cascade inhibitor. We established a new porcine model of IRI by cross-clamping the thoracic aorta and evaluated the global changes occurring in organ function, systemic inflammatory response and organ damage with or without treatment with C1-INH-concentrate. Twenty-four piglets (8.8-11.1 kg) underwent 45 minutes clamping of the thoracic aorta at the Th8 level. Upfront 12 piglets received human saline and 12 received C1-INH (250 IU/kg) intravenously. Three sham animals received thoracic opening without clamping. Reperfusion lasted 5 hours. We studied ten cardiorespiratory markers, three hematologic markers, eleven inflammatory markers, and twelve organ damage markers over the whole experimental period. Postmortem tissue homogenates from seven organs were examined for inflammatory markers and analysed by two-way repeated-measures ANOVA, area under the curve or unpaired t-tests. By excluding sham and combining treated and untreated animals, the markers reflected a uniform, broad and severe organ dysfunction. The mean and range fold change from before cross-clamp onset to maximum change for the different groups of markers were: cardiorespiratory 1.4 (0.2-3.7), hematologic 1.9 (1.2-2.7), plasma inflammatory 19.5 (1.4-176) and plasma organ damage 2.9 (1.1-8.6). Treatment with C1-INH had only a marginal effect on the IRI-induced changes, reaching statistical significance only for the plasma complement activation product TCC (p=0.0083) and IL-4 (p=0.022) and INF-α (p=0.016) in the colon tissue. In conclusion, the present novel model of porcine global IRI is forceful with regard to central markers and could generally be applicable for pathophysiological studies. C1-INH treatment had no significant effect, but the model allows for future testing of other drugs attenuating IRI globally.